MENGEMBANGKAN KREATIVITAS ANAK MELALUI PENTAS SENI TARI DAN DRAMA DI RA NURUL ISLAM BUNGO - Wiwin Narti; Sumiyati; Munahayati, Safira; Lisaini; Nursafika, Intan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creativity in early childhood is an essential aspect that should be developed from an early age because it forms the basis for thinking, imagination, and self-expression. However, in many early childhood education institutions, learning activities that stimulate creativity are still limited. Based on preliminary observations at RA Nurul Islam Bungo, most children tended to be passive during art activities and lacked confidence to perform in front of their peers. This study aims to develop children’s creativity through art performances in dance and drama as enjoyable and meaningful learning media. The research used a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The results showed that stage art activities effectively foster children’s confidence, courage, and ability to express ideas creatively. In addition, children demonstrated improvement in cooperation, discipline, and responsibility throughout the rehearsal and performance process. Therefore, dance and drama performances not only enrich the learning experience but also serve as effective tools to develop children’s creative potential and positive character within the RA environment.